IDENTIFIKASI KAWASAN ZONA PANAS BUMI (GEOTHERMAL) DI DAERAH X MENGGUNAKAN METODE MAGNETOTELLURIK - Andini, Dela; Lepong, Piter; Natalisanto, Adrianus Inu (Geophysics Study Program, Faculty of Mathematics and Natural Sciences, Mulawarman University, 2020)
Geothermal is the heat formed inside the earth's crust. The heat of geothermal produces hot water, steam, and heat rocks along with other minerals and gases to be genetically inseparable in geothermal systems. One of the geophysical method which can be used to determine the area of a geothermal system is magnettoteluric. The method is based on the values of resistivity distribution of the rock formation. In the study on the identification of geothermal zone in the X area, it was found the resistivity distribution in 1D and 2D models by using the magnettoteluric method. The models were created by processing of magnettoteluric data taken from three measuring lines. The 1D model was the resistivity distribution vertically generated from the depth of each measurement point, while the 2D model was the resistivity distribution generated in vertical and lateral to form the image of geothermal system. In the 1D model the resistivity distribution values were in the range of 66 ohm.m and 270 ohm.m, while in the 2D model the resistivity distribution values were in the range of 66 ohm.m and 221 ohm.m. From the image it could be interpreted the low resistivity related to the cap rock zone located above the reservoir zone, the medium resistivity related to the reservoir zone located below the cap rock zone, and the high resistivity related to the heat source zone located below the reservoir zone. The study found that the position of geothermal reservoir was under the cap rock zone.